A patient-centered hospital in Malaysia in accordance with Maqasid Syariah principles: a comprehensive review and prospective research directions - Ahmad Luqmanulhakim Sunawari,; Azira Khalil,; Madihah Mat Idris,; Azlina Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper presents a comprehensive review and proposes prospective research directions for the establishment of a patient-centered hospital in Malaysia that aligns with the principles of maqasid syariah. The integration of maqasid syariah, which encompasses the higher objectives and goals of Islamic law, with patient-centered care aims to create a healthcare environment that prioritizes the well-being and needs of patients while adhering to Islamic ethical principles. The review encompasses an analysis of the key principles of maqasid syariah, including the preservation of life, human dignity, justice, and holistic well-being. These research directions encompass various aspects, including healthcare facility design, communication strategies, equitable access to care, ethical considerations, and the integration of spirituality in healthcare. The outcomes of this research are expected to contribute to the advancement of healthcare practices in Malaysia by integrating Islamic values and patient-centered care principles in developing a framework that can be done in future. The proposed patient-centered hospital will not only provide high-quality care but also ensure the preservation of life, uphold human dignity, promote justice, and address the holistic well being of patients.